PfAP2-EXP2, an Essential Transcription Factor for the Intraerythrocytic Development of Plasmodium falciparum - Shang, Xiaomin; Wang, Changhong; Shen, Li; Sheng, Fei; He, Xiaohui; Wang, Fei; Fan, Yanting; He, Xiaoqin; Jiang, Mei (Frontiers in Cell and Developmental Biology, 2022)
Plasmodium falciparum undergoes a series of asexual replications in human erythrocytes after infection, which are effective targets for combatting malaria. Here, we report roles of an ApiAP2 transcription factor PfAP2-EXP2 (PF3D7_0611200) in the intraerythrocytic developmental cycle of P. falciparum. PfAP2-EXP2 conditional knockdown resulted in an asexual growth defect but without an appreciable effect on parasite morphology. Further ChIP-seq analysis revealed that PfAP2-EXP2 targeted genes related to virulence and interaction between erythrocytes and parasites. Especially, PfAP2-EXP2 regulation of euchromatic genes does not depend on recognizing specific DNA sequences, while a CCCTAAACCC motif is found in its heterochromatic binding sites. Combined with transcriptome profiling, we suggest that PfAP2-EXP2 is participated in the intraerythrocytic development by affecting the expression of genes related to cell remodeling at the schizont stage. In summary, this study explores an ApiAP2 member plays an important role for the P. falciparum blood-stage replication, which suggests a new perspective for malaria elimination.